2021
DOI: 10.1016/j.cgh.2021.06.046
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Sequelae 3 and 6 Months After Hospitalization for Coronavirus Disease 2019

Abstract: G astrointestinal Q5(GI) symptoms are highly prevalent in coronavirus disease 2019 (COVID-19) ranging from 17.6 % to 53 %. [1][2][3][4] The proposed mechanism for GI symptoms involves SARS-CoV-2 virus binding to the host cell's angiotensin-converting enzyme-2 receptor, commonly found in GI tract epithelial cells. 5 With an increasing population of patients recovering from acute infection, there is now interest in understanding post-COVID-19 sequelae. Our study aims to report GI sequelae 3 and 6 months after ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 9 publications
(2 reference statements)
2
28
0
4
Order By: Relevance
“…Those patients with weight loss had greater systemic inflammation, impaired renal function and longer disease duration. A large, multicenter study (including 3,229 patients with GI symptoms) showed that 23% of patients had malnutrition, of whom 56.4% were unable to gain weight after 6 months follow-up ( Rizvi et al, 2021 ). Studies also showed that malnutrition was associated with higher incidences of acute respiratory distress syndrome, acute myocardial injury, secondary infection, shock, and 28-day ICU mortality ( Luo et al, 2020 ; Zhang P. et al, 2021 ).…”
Section: Intestinal Damage Malnutrition and Poor Outcomesmentioning
confidence: 99%
“…Those patients with weight loss had greater systemic inflammation, impaired renal function and longer disease duration. A large, multicenter study (including 3,229 patients with GI symptoms) showed that 23% of patients had malnutrition, of whom 56.4% were unable to gain weight after 6 months follow-up ( Rizvi et al, 2021 ). Studies also showed that malnutrition was associated with higher incidences of acute respiratory distress syndrome, acute myocardial injury, secondary infection, shock, and 28-day ICU mortality ( Luo et al, 2020 ; Zhang P. et al, 2021 ).…”
Section: Intestinal Damage Malnutrition and Poor Outcomesmentioning
confidence: 99%
“…1 However, limited data exist on GI sequelae that might be present in COVID recovered patients on follow-up. In a recent study, Rizvi et al 4 have described the resolution of the initial GI manifestations in more than 90% of the cases on 3 and 6-month follow-up in a retrospective study of a large cohort of patients. In our prospective study we observed that GI sequelae persist in around 16% of the patients, on 3month follow-up.…”
Section: Dear Editormentioning
confidence: 99%
“…The factors predicting the persistence of GI sequelae would be an interesting observation. Rizvi et al [4] did not look into these factors. Weng et al [5] , in their study, found that patients with GI sequelae had less severe disease (17% vs. 37%) compared to those who did not have GI sequelae.…”
mentioning
confidence: 99%
“…Previous studies reported a prevalence of gastrointestinal post‐COVID symptoms ranging from 10% to 25%. 4 , 5 Most studies investigating post‐COVID gastrointestinal symptoms used cross‐sectional designs. Since the presence of long‐term post‐COVID symptoms is associated with lower quality of life, 6 understanding the longitudinal pattern of gastrointestinal symptoms could have significant implications for diagnosis, triaging, and management of these patients.…”
Section: Figurementioning
confidence: 99%
“…Our prevalence rates of post‐COVID gastrointestinal symptom agree with previous data. 4 , 5 Nevertheless, most studies included smaller samples, data from single centers, and shorter follow‐up periods. 4 , 5 At hospital admission, the presence of diarrhea was noted but not the gastrointestinal symptoms since most patients specified only diarrhea.…”
Section: Figurementioning
confidence: 99%